Analysis Of Students' Mathematical Literacy Ability In Solving Pisa-Oriented Questions Content Change And Relationship Judging From Self-Efficacy - Mumfaza, Risqia; Setyaningsih, Rini (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Study This aims to analyze the connections between the ability of literacy mathematical students to finish questions on PISA Change and relationships, which are oriented on content and levels of efficiency. Study This uses design study descriptive qualitative. The sample for this research consisted of three class VIII B students at SMPN 3 Colomadu, Karanganyar Regency. The three subjects were selected based on the results of responses to the questionnaire and PISA questions, taking into account their level of self-efficacy, which was divided into low, medium, and high. The research instrument consisted of a questionnaire regarding student self-efficacy and PISA questions related to Change and Relationship content. After analyzing the questionnaire and students' answers, they interviewed the three subjects. The research results show that students' mathematical literacy skills in solving questions oriented towards changes in PISA content and their interrelationships require improvement. The level of students' self-efficacy in solving mathematics literacy problems is classified as moderate, and there is a significant positive relationship between mathematics literacy abilities and students' self-efficacy.